2024
DOI: 10.5267/j.uscm.2023.9.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of green supply chain management practices on performances of herb manufacturers in Thailand

Wissawa Aunyawong,
Phutthiwat Waiyawuththanapoom,
Phitphisut Thitart
et al.

Abstract: This research aimed to 1) investigate the levels of green supply chain management practices (GSCMP), environmental performance (ENP), operational performance (OPP), and organizational performance (ORP) in the context of Thai herb producers; and 2) investigate the interactions between GSCMP, ENP, OPP, and ORP. Quantitative research methodologies were applied in the research. The sample for the quantitative study consisted of 340 Thai herb producers selected by stratified sampling by region. The instruments empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Internal integration, as highlighted by Tiwari [75], facilitates the integration of all internal functions within an organization, resulting in improved communication and efficient decision-making processes [76]. By enabling the sharing of information, internal integration plays a crucial role [77], on the other side, operational integration between SC partners enhances SCR in response to disturbances [74]. Related to this, a study conducted in Taiwan by Liu and Lee [78] demonstrated that both internal integration and customer integration, which are forms of SCI, have a significant positive impact on SCR, particularly within third-party logistics providers.…”
Section: Blockchain Technology Supply Chain Integration and Supply Ch...mentioning
confidence: 99%
“…Internal integration, as highlighted by Tiwari [75], facilitates the integration of all internal functions within an organization, resulting in improved communication and efficient decision-making processes [76]. By enabling the sharing of information, internal integration plays a crucial role [77], on the other side, operational integration between SC partners enhances SCR in response to disturbances [74]. Related to this, a study conducted in Taiwan by Liu and Lee [78] demonstrated that both internal integration and customer integration, which are forms of SCI, have a significant positive impact on SCR, particularly within third-party logistics providers.…”
Section: Blockchain Technology Supply Chain Integration and Supply Ch...mentioning
confidence: 99%